The status of neglected tropical diseases amidst COVID-19 in Africa: Current evidence and recommendations - Rafiat Tolulope Akinokun; Esther Bosede Ilesanmi; Yusuff Adebayo Adebisi; Oluwadamilare Akingbade (Tabriz University of Medical Sciences, 2021)
Health care services and programs directed towards combating the neglected tropical diseases (NTDs) have been disrupted because of the impact of the coronavirus disease 2019 (COVID-19). The African continent because of its staggering health care system and poor economy disproportionately bears the burden of these diseases. While successes have been recorded in controlling and eliminating the NTDs, policymakers in Africa should consider the potential of the COVID-19 to dwindle these successes an issue of high priority. This commentary seeks to discuss the current status of NTDs in Africa and proffer recommendations to help combat these diseases at this period. It is worthy to say that similar dedication directed towards fighting the COVID-19 should also be deployed into eliminating other diseases like the NTDs which often, are neglected.